Synthesis of the Main Red Wine Anthocyanin Metabolite: Malvidin-3-O-β-Glucuronide - Cruz, Luís; Fernandes, Iva; Évora, Ana; de Freitas, Victor; Mateus, Nuno (Synlett, 2017)
Anthocyanins are widely consumed in human and despite the health effects that have been attributed to them they appear to have low plasmatic concentration. This is in great part attributed to the lack of standards to allow an adequate assignment of the identity of the compounds detected that are often not the ones present in the original source. In this work, the chemical synthesis strategy of one of the glucuronide conjugates of the main anthocyanin present in red wine was developed. The purity and the identity of the metabolite were checked by HPLC-DAD, LC-MS, and NMR spectroscopy. It was confirmed that the compound obtained was malvidin-3-O-β-glucuronide, with the main MS2 and MS3 fragments corresponding to the loss of glucuronic moiety [M – 176]+m/z = 331 and methyl groups [M – 176 – 16]+m/z = 315. The configuration and the position of the linkage between the aglycone and the glucuronyl residue was confirmed by NMR spectroscopy, considering the coupling constant between H-C1′′ and H-C2′′ and HMBC/NOESY connectivities.
Keywords: anthocyanins; metabolites; red wine; glucuronidation; chemical synthesis